Understanding Reactivity Patterns in Light‐Induced Nitrile Imine Mediated Tetrazole–Ene Cycloadditions. Issue 5 (25th January 2017) - Blasco, Eva; Sugawara, Yuuki; Lederhose, Paul; Blinco, James P.; Kelterer, Anne‐Marie; Barner‐Kowollik, Christopher
Abstract: A rationale for predicting photochemical tetrazole activation in the popular nitrile imine mediated tetrazole–ene cycloaddition (NITEC) reaction, based on a combined theoretical and experimental study, is reported. DFT calculations of three tetrazole derivatives reveal that the efficiency of intersystem crossing is determined by the chromophore moiety. This species is critical in dictating the reactivity of the tetrazoles towards nitrile imine formation, yet mere inspection of the chromophore moiety's absorptivity is insufficient for predicting the tetrazole's photochemical reactivity. Abstract : Collecting clues : A combined theoretical and experimental study to predict photochemical tetrazole activation in nitrile imine mediated tetrazole–ene cycloadditions (NITEC) is presented. DFT calculations of three tetrazole derivatives reveal that the efficiency of intersystem crossing as well as the charge distribution in the excited states are critical for the reactivity of the tetrazoles and are in excellent agreement with experimental observations.